A healthy Nordic diet and physical performance in old age: findings from the longitudinal Helsinki Birth Cohort Study. Issue 5 (20th January 2016) - Perälä, Mia-Maria; von Bonsdorff, Mikaela; Männistö, Satu; Salonen, Minna K.; Simonen, Mika; Kanerva, Noora; Pohjolainen, Pertti; Kajantie, Eero; Rantanen, Taina; Eriksson, Johan G.
Abstract: Epidemiological studies have shown that a number of nutrients are associated with better physical performance. However, little is still known about the role of the whole diet, particularly a healthy Nordic diet, in relation to physical performance. Therefore, we examined whether a healthy Nordic diet was associated with measures of physical performance 10 years later. We studied 1072 participants from the Helsinki Birth Cohort Study. Participants' diet was assessed using a validated 128-item FFQ at the mean age of 61 years, and a priori -defined Nordic diet score (NDS) was calculated. The score included Nordic fruits and berries, vegetables, cereals, PUFA:SFA and trans -fatty acids ratio, low-fat milk, fish, red and processed meat, total fat and alcohol. At the mean age of 71 years, participants' physical performance was measured using the Senior Fitness Test (SFT), and an overall SFT score was calculated. Women in the highest fourth of the NDS had on average 5 points higher SFT score compared with those in the lowest fourth ( P for trend 0·005). No such association was observed in men. Women with the highest score had 17 % better result in the 6-min walk test, 16 % better arm curl and 20 % better chair stand results compared with those with the lowest score (all P values<0·01). In conclusion, a healthy Nordic diet was associated with better overall physical performance among women and might help decrease the risk of disability in old age.